Pengaruh Model Pembelajaran ARIAS (Assurance, Relevance, Interest, Assessment, and Satisfaction) dalam Meningkatkan Hasil Belajar IPA Siswa di Sekolah Dasar - Cindy Putri Wanningrum; Wati Sukmawati (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This study aims to determine the effect of the ARIAS (Assurance, Relevance, Interest, Assessment, and Satisfaction) learning model on student learning outcomes. Quantitative research using Posttest Only Control Group Design or also known as Quasi Experimental Design. Saturated sampling was used to select 30 students who became research respondents. There were 25 multiple choice questions included in the instrument. The test was used to obtain Posttest value data. Point Biserial correlation formula and reliability calculation will be used to validate the instrument beforehand. With a score of 84.7 the control class performed worse than the experimental class. Data were analyzed by t-test. The t-test results showed that students science learning outcomes increased with the application of the ARIAS learning model in elementary school.